2016
DOI: 10.1093/ajcp/aqv085
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Papanicolaou Tests in the Diagnosis of Endometrial Carcinoma

Abstract: The Pap test may play a role in the detection of endometrial carcinoma, especially for those with cervical involvement, lymphovascular invasion, and/or advanced stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…[ 3 ] Several studies have scrutinized the value of preoperative cervical cytology in EC in terms of screening, prognostic marker of clinicopathological outcomes, and survival. [ 5 6 7 8 9 10 11 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 3 ] Several studies have scrutinized the value of preoperative cervical cytology in EC in terms of screening, prognostic marker of clinicopathological outcomes, and survival. [ 5 6 7 8 9 10 11 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that preoperative cervical cytology significantly correlated with numerous clinicopathological parameters in patients with EC [ Table 3 ]. [ 5 6 7 8 9 10 11 14 ] Examples of such parameters included tumor histology, tumor grade, tumor stage, depth of MI, lymph node involvement, cervical involvement, peritoneal washing, and LVSI. The findings of our study matched the findings of earlier reports only with regard to tumor grade and cervical involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] Upon review of current English literature, only rare case reports of metastatic EMCA and a single case series of endometrial cancers which included 3 endometrioid adenocarcinoma subtypes sampled by FNA [8][9][10][11][12] have been reported. 17 In extremely rare instances, evidence of EMCA has been found on urine cytology. 13,14 Studies describing endometrial adenocarcinoma on cervical pap smears (generally without mention of the histologic subtype) have reported glandular structures with nuclear enlargement, conspicuous nucleoli, scant vacuolated cytoplasm, and occasional squamous differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Interestingly, endometrial carcinomas with serous or clear cell histologies have a higher likelihood of having abnormal Pap smears than EMCAs. 17 In extremely rare instances, evidence of EMCA has been found on urine cytology. 18 Cytologic endometrial sampling by endometrial aspiration via catheters or cannula 19,20 has been described, but these reports are limited in number and do not provide detailed cytomorphologic features of encountered malignancies.…”
Section: Introductionmentioning
confidence: 99%